Human Resource Management Strategies to Enhance Sustainable Corporate Performance in Industry 4.0 - Dipoatmodjo, Tenri Sayu Puspitaningsih (PT. Maju Malaqbi Makkarana, 2024)
In the Industry 4.0 era, achieving sustainable business success requires organizations to harness unique, rare, and inimitable resources. These resources demand a long learning curve within the organization and are critical for sustaining competitive advantage. This study explores the Era 4.0 Organizational Sustainability Model, a hybrid framework that demonstrates the interrelation of key organizational elements, including core competencies, business outcomes, and strategic objectives essential for long-term operational sustainability. In a landscape of intense competition, survival and growth are imperative goals for organizations. Central to this endeavor is the management of human resources, particularly the Millennial workforce, known for its unique challenges in turning weaknesses into opportunities for development. This research highlights the critical role of tailored talent management strategies in addressing generational characteristics, fostering employee growth, and aligning workforce capabilities with organizational needs. By employing an innovative and holistic HR strategy, organizations can enhance their ability to compete sustainably while driving long-term profitability and resilience in the face of rapid technological and market changes.